2012
DOI: 10.1007/s11999-012-2403-7
|View full text |Cite|
|
Sign up to set email alerts
|

MRI of Hip Cartilage: Joint Morphology, Structure, and Composition

Abstract: Background Accurate, reproducible, and noninvasive assessment of hip cartilage is clinically relevant and provides a means by which to assess the suitability of candidates for arthroscopic or open surgical procedures and the response to such interventions over time. Given the relatively thin cartilage of the hip and the complex spherical anatomy, however, accurately assessing the cartilage poses a challenge for traditional MRI techniques. Questions/Purposes We assessed the current status of imaging articular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 24 publications
0
53
0
2
Order By: Relevance
“…Novel biochemical MRI modalities may allow evaluation of cartilage biochemistry long before cartilage loss occurs [5,10]. Among others, noncontrast biochemical MRI techniques include T2 and T2* mapping sequences [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Novel biochemical MRI modalities may allow evaluation of cartilage biochemistry long before cartilage loss occurs [5,10]. Among others, noncontrast biochemical MRI techniques include T2 and T2* mapping sequences [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Sagittal images are primarily used for the detection of labral abnormalities; they are also particularly suitable for the evaluation of the weightbearing portion of the cartilage of the femoral head and acetabular dome [2]. These regions are prone to cartilage lesions, especially in patients with FAI, avascular necrosis, and insufficiency fractures, and therefore should be assessed with special attention [15,37,38].…”
Section: Sequencesmentioning
confidence: 99%
“…In a study by Kassarjian et al [73], anterosuperior cartilage lesions were found in 95% (40/42) of the patients. Patients with symptomatic FAI typically have rapid cartilage loss over the anterosuperior margin of the dome and active delamination may be seen, which is manifested as hyperintensity in the basilar component of the cartilage over the anterior dome extending down to the tidemark [2,24]. Figures 5-7 show examples of arthroscopically proven carpet lesion or delaminating lesion in patients with FAI.…”
Section: Regional Abnormalities Of the Hip: What Are The Disease Entimentioning
confidence: 99%
See 2 more Smart Citations